Impact of free hypertension pharmacy program and social distancing policy on stroke: A longitudinal study - Zhou, Qi; Yu, Meihua; Jin, Meihua; Zhang, Peng; Qin, Guoyou; Yao, Ye (Frontiers in Public Health, 2023)
Background: The estimated lifetime risk of stroke was the highest in East Asia worldwide, especially in China. Antihypertensive therapy can significantly reduce stroke mortality. However, blood pressure control is poor. Medication adherence is a barrier as patients’ out-of-pocket costs have risen. We aimed to take advantage of a free hypertension pharmacy intervention and quantified the impact on stroke mortality. Methods: A free pharmaceutical intervention program was implemented in Deqing, Zhejiang province in April 2018. Another non-pharmaceutical intervention, social distancing due to the pandemic of Coronavirus disease 2019 (COVID-19), was also key to affecting stroke mortality. We retrospectively collected the routine surveillance data of stroke deaths from Huzhou Municipal Center for Disease Prevention and Control in 2013-2020 and obtained within-city mobility data from Baidu Migration in 2019-2020, then we quantified the effects of both pharmaceutical intervention and social distancing using Serfling regression model. Results: Compared to the predicted number, the actual number of stroke deaths was significantly lower by 10% (95% CI, 6% - 15%; P < 0.001) from April 2018 to December 2020 in Deqing. Specifically, there was a reduction of 19% (95% CI, 10% - 28%; P < 0.001) in 2018. Moreover, we observed a 5% (95% CI, -4% - 14%; P = 0.28) increase in stroke mortality due to the adverse effect of COVID-19 but it wasn’t statistically significant. Conclusions: Free hypertension pharmacy program has great potential to prevent considerable stroke deaths. In the future, the free supply of low-cost, essential medications that target patients with hypertension at increased risk of stroke could be taken into account in formulating public health policies and guiding allocations of health care resources.